Loop induced type-II seesaw model and GeV dark matter with U(1)B−L gauge symmetry - Takaaki Nomura; Hiroshi Okada (Physics Letters B, 2017)
We propose a model with U(1)B−L gauge symmetry and several new fermions in no conflict with anomaly cancellation where the neutrino masses are given by the vacuum expectation value of Higgs triplet induced at the one-loop level. The new fermions are odd under discrete Z2 symmetry and the lightest one becomes dark matter candidate. We find that the mass of dark matter is typically O(1)-O(10) GeV. Then relic density of the dark matter is discussed.